Perspectives Of Deep Ecological Principles In Annie Proulx's Barkskins (International Journal of Environmental Sciences, 2025)
Deforestation remains one of the crucial environmental issues that the world faces today. Rapid deforestation substantially contributes to a broad range of environmental consequences, like biodiversity loss and global surface temperature rise. Forests are among the pivotal components that regulate and determine an area's climate and weather conditions, and they also challenge the viability of creatures such as humans, flora, and fauna, as well as combat illegal logging. This paper will analyze the deep ecological principles that align with the novel. It illustrates the value of primitive species of plants and animals. It explores whether humans have realized the natural world's value, richness, and diversity. It discloses whether humans use nature and nonhumans for their vital needs or has overridden the usage. It delineates the flourishing of human life and culture and examines the compatibility of the human population through the tremendous consumption and waste production rate. It investigates the repercussions of human interference with the nonhuman world. The policies that have changed to ensure the sustenance of living beings. It enquires about the ideological change appreciating the quality of life rather than adhering to a high standard of living.